Prevention of enterotoxacmiu in transported cattle - Lily Natalia; Sudarisman .; M Darodjat (Jurnal Ilmu Ternak dan Veteriner, 1996)
Fatal enterotoxaemia of transported cattle is frequently reported in Indonesiu. Acute enteritis and fatal enterotoxaemia of cattle and buffaloes in Indonesia are associated with toxigenic Clostridium perfringenr type A. The outbreaks could have been caused by some kinds of stress, such as a possible change in nutrition or management as well as transportation . To reduce mortality rate caused by enterotoxaemia, an effective vaccine against the disease was produced . The vaccine was made in an alum precipitated toxoid form, prepared from Clostridlumperfringens type A  toxin, which was then tested for safety in mice and for its capacity in generating high immunity in cattle. The vaccine was then used to immunise transported cattle as an attempt to reduce mortality rate and to observe antibody response of cattle following vaocletdon. The results showed that mortality in vaccinated was lower than in non-vaccinated groups of cattle. From field observation, it was obvious that alum precipitated toxoid vaccine could produce good immune response against enterotoxaemia in cattle . It was also evidence that this vaccine could reduce mortality in transported cattle .   Keywords: Enterotoxaemia, vaccine, transportation, cattle